2019
DOI: 10.1093/nar/gkz095
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the ATM/autophagy pathway by a G-quadruplex ligand tips the balance between senescence and apoptosis in cancer cells

Abstract: G-quadruplex ligands exert their antiproliferative effects through telomere-dependent and telomere-independent mechanisms, but the inter-relationships among autophagy, cell growth arrest and cell death induced by these ligands remain largely unexplored. Here, we demonstrate that the G-quadruplex ligand 20A causes growth arrest of cancer cells in culture and in a HeLa cell xenografted mouse model. This response is associated with the induction of senescence and apoptosis. Transcriptomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 80 publications
1
45
0
Order By: Relevance
“…Another factor that regulates the lysosomal size and number is the TFEB transcription factor, which is responsible for the induction of genes encoding lysosomal proteins through a mechanism that depends on mTOR inhibition [32,33]. The fact that 20A causes the upregulation of several genes encoding for lysosomal proteins and inhibition of mTOR (as shown in our previous works [24,34] and Figure S1) argues in favor of the activation of the TFEB protein in response to 20A. It would be interesting to determine if and how TFEB regulates lysosome functions and cell death in cells exposed to 20A alone or with chloroquine.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Another factor that regulates the lysosomal size and number is the TFEB transcription factor, which is responsible for the induction of genes encoding lysosomal proteins through a mechanism that depends on mTOR inhibition [32,33]. The fact that 20A causes the upregulation of several genes encoding for lysosomal proteins and inhibition of mTOR (as shown in our previous works [24,34] and Figure S1) argues in favor of the activation of the TFEB protein in response to 20A. It would be interesting to determine if and how TFEB regulates lysosome functions and cell death in cells exposed to 20A alone or with chloroquine.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously shown that 20A, a G-quadruplex ligand belonging to the triarylpyridine family, exerts potent cytotoxic and cytostatic effects on several cancer cells. We found that one of the gene classes most significantly upregulated by 20A corresponds to the autophagy lysosomal pathway [24].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Small molecules capable of stabilizing G4 can trigger DNA double-strand breaks and induce DNA damage response (DDR) and cell death. [5] Because G4s contain the G-quartet as a common structural feature, ligands can stabilize more than one G4 target present in different promoters. One such example is quarfloxin (CX-3543), which shows selectivity for parallel G4s, such as c-MYC [6] and VEGF.…”
mentioning
confidence: 99%